2020
DOI: 10.1089/neu.2019.6595
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Pursuit and Saccades after Sport-Related Concussion

Abstract: Smooth pursuit eye movements (SPEMs) and saccadic eye movements are both commonly impaired following sportrelated concussion (SRC). Typical oculomotor assessments measure individual eye movements in a series of restrictive tests designed to isolate features such as response times. These measures lack ecological validity for athletes because athletes are adept at simple tasks designed for the general population. Yet, because eye movement metrics are sensitive and well-characterized neuroanatomically, it would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
0
29
4
Order By: Relevance
“…Several authors have reported significant postconcussive deficits in vertical saccades. 23 , 25 , 30 , 45 It is unclear why vertical saccade metrics were not statistically significant classifiers in our study. Small sample size combined with the relatively conservative Bonferonni method of correcting for multiple comparisons may have obscured a statistically significant group difference.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Several authors have reported significant postconcussive deficits in vertical saccades. 23 , 25 , 30 , 45 It is unclear why vertical saccade metrics were not statistically significant classifiers in our study. Small sample size combined with the relatively conservative Bonferonni method of correcting for multiple comparisons may have obscured a statistically significant group difference.…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, the reliability of reaction time measures on the device used in our study was quite robust among noninjured young adults, with most intraclass correlation coefficients above 0.75. 54 Because visual reaction time and other eye movement performance metrics are faster and more accurate in athletes than nonathletes 23 and decline with advancing age, [54][55][56] our results may not be generalizable to older or nonathlete populations. Furthermore, although observers were not masked to patient grouping, neither ET nor cognitive testing are subjective measures, likely limiting the effect of observer bias.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, saccadic eye movement training in web game playing is often used to reduce the abnormal occurrence, such as longer anti-saccade latencies and lower pro-saccade accuracy [42]. In addition, it has been used after a sports-related concussion to restore saccadic amplitude and velocity [61].…”
Section: Common Regarded Gaze Parameters Within Sports-related Purposesmentioning
confidence: 99%
“…Murray et al [26] SPEM after concussion Case-control (N=36) Abnormalities in SPEM amplitude and velocity were associated with concussion vs control groups.…”
Section: Smooth Pursuit Eye Movement Dysfunctionmentioning
confidence: 99%